A step toward essential tremor gene discovery: identification of extreme phenotype and screening of HTRA2 and ANO3. Issue 1 (December 2016) - Renaud, Mathilde; Marcel, Christophe; Rudolf, Gabrielle; Schaeffer, Mickaël; Lagha-Boukbiza, Ouhaïd; Chanson, Jean-Baptiste; Chelly, Jamel; Anheim, Mathieu; Tranchant, Christine
Abstract Background Essential tremor (ET) is characterized by a frequent family history. No monogenic form of ET has been identified. We aimed at exploring ET patients to identify distinct subgroups and facilitate the identification of ET genes. We tested for the presence ofHTRA2 p.G399S, andANO3 p. W490C, p. R484 W and p. S685G mutations. Methods Between June 2011 and November 2013, all consecutive patients suspected with ET were prospectively included in a prospective, monocentric study. Family history, age at onset (AAO), features of tremor, benefit of alcohol and drugs, electrophysiological recording findings were collected. Sanger sequencing was performed forHTRA2 andANO3 mutations screening. Results Sixty eight patients were investigated. Fourteen diagnosed with psychogenic (5) or dystonic tremor (9) were excluded. Regarding the 54 ET patients, mean AAO was 48 years (6–77), and mean disease duration 15 years (1–55). Bimodal distribution of AAO was consistent with phenotypic subgroups. In patients with AAO before 30 years, marked benefit of alcohol (p  < 0.01) and ET family history (p  < 0.01) were more frequent and the disease progression less severe (p  < 0.0001). NeitherHTRA2 norANO3 mutation were identified in our patients. Conclusions Our data support that distinct ET phenotypic subgroups may be encountered. We recommend to study separately extreme phenotypes of ET, particularly autosomal dominant families with early AAO (<30 years) and marked benefit of alcohol, to facilitate the identification of ET genes. Electromyographic recording remains a support to distinguish ET from differential diagnosis.HTRA2 andANO3 mutations are not common causes of ET.